European minimum standards for obstetric analgesia and anaesthesia departments: An experts' consensus. Issue 12 (December 2020) - Guasch, Emilia; Brogly, Nicolas; Mercier, Frederic J.; Ioscovich, Alexander; Weiniger, Carolyn F.; Lucas, Nuala; Chassard, Dominique; Kranke, Peter; Whitaker, David; Geldner, Goetz; Sabelnikovs, Olegs; de Robertis, Edoardo
Abstract : N/A: An important variability of anaesthetic standards of care was discovered in the obstetric departments of many European Union countries. After discussing this issue in various meetings of the European Society of Anaesthesiology (ESA) board and its obstetric subcommittee, European Board of Anaesthesiology of the European Union of Medical Specialists (EBA-UEMS) executive members, ESA obstetric subcommittee members and European experts in obstetric anaesthesiology have participated in the elaboration of this document. This experts' opinion is focused mainly on obstetric patients and safety concerns in terms of minimum standards of practice. An initial bibliographical search was performed in medical databases and general literature, searching for obstetric anaesthesiology standards to select the most important safety issues. After the initial presentation of the project during EBA-UEMS and ESA obstetric subcommittee meetings, participants were asked to review the document; several rounds of revisions were performed by the experts, to reach a common opinion concerning the topics considered central to patient safety in the obstetric setting. After three rounds of revision, a consensus was reached and is presented in this document, which includes the list of topics considered relevant by the involved areas, and the respective recommendations. These recommendations covered some EBA-UEMS strategic key areas, in addition to several clinical aspects of common obstetric practice.